Governance of cooperatives: literature review’s benchmark - RIAD , Oumaima; SAOUD , Sahar; AZAMI HASANI , Khalid (Revue Internationale des Sciences de Gestion, 2023)
This paper presents the theoretical contributions of cooperatives’ governance. The theoritacal literature of cooperatives’ governance is undeveloped in comparaison with that on corporate governance. In this vein, the paper proceeds to extract the points of convergence and divergence between the theoretical perspectives of cooperatives’governance based on 24 scientifics studies in the fields. This Comparaison allows to illustrate a theoretical framework of governance that concerns all cooperatives. Indeed, the main point of convergence is that the cooperatives ‘governance is based on the bringing together a set of theories of corporate governance even if they are contradictory: multi-paradigmatic paradox. According to the contributions, this paradox is explained differently but the principle of bringing together the theories of corporate governance remains the same. This leads us to make a critical reading of all the contributions that have studied the governance of cooperatives before and to propose our research perspectives wich is the innovative value of this literature review.